Hubungan Sikap, Dukungan Keluarga Dan Pola Asuh Terhadap Status Gizi Balita Usia 6-24 Bulan Di Puskesmas Menes: Relationship between Attitude, Family Support and Parenting Patterns on the Nutritional Status of Toddlers Age 6-24 Months at the Menes Community Health Center - Rafa, Mardiah (Dohara POAJ, 2022)
Introduction: In general, the problem of under-five malnutrition is still quite high, it can be calculated on the Weight/Height indicator which describes the acute nutritional status as a result of conditions that last for a short time, such as decreased appetite due to illness, or suffering from diarrhea. The purpose of the study was to determine the relationship between the level of attitude, family support, and parenting on the nutritional status of children aged 6-24 months at the Menes Health Center. Methods: The design of this research is descriptive-analytic with a cross-sectional approach. The population used in this study were mothers who visited PKM baby care in Menes District, Pandeglang Regency as many as 110 mothers. Meanwhile, in taking the sample, the writer used the Slovin formula to obtain as many as 87 samples. Researchers used the Chi-Square test. Results: The results of the study showed that there was a univariate relationship between attitude and nutritional status in toddlers aged 6-24 months. Discussion: After doing the research, the researcher suggests to several parties, namely mothers, it is hoped that they can increase knowledge, especially regarding nutritional status.